Bandwidth requirement for suppression of grating lobes in ultrawideband antenna arrays - Sipal, V; Edwards, D; Allen, B (2012)
Sparse ultrawideband antenna arrays suppress the grating lobes due to the fact that the duration of pulses processed by individual antenna elements is too short to constructively superpose them in the time domain. Such arrays represent an attractive option for design of many low-comlexity low-cost ultrawideband systems, where narrow beamwidth is achieved by increase of element spacing. This paper empirically explores the minimum bandwidth required for suppression of the grating lobes. It is found that the relative bandwidth required to suppress grating lobes is independent on the centre frequency, element spacing, and number of elements. There is a weak dependency of the bandwidth on the type of the pulse used, but the general conclusion is that the relative bandwidth has to exceed 100% in order to suppress the grating lobes. It is, however, noted that whilst sparse array with a low number of antenna elements can suppress the grating lobes and posses a narrow beam, the compromise for this feature is a reduction of the level of spatial filtering between the main lobe and other directions, when compared to arrays where grating lobes are suppressed by dense spacing. © 2012 IEEE.